2021
DOI: 10.1021/acs.jced.0c01029
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of Aqueous Two-Phase Systems of PEG with Sulfate Salt: Effects of pH, Temperature, Type of Cation, and Polymer Molecular Weight

Abstract: The present work reports the liquid–liquid equilibrium (LLE) measurements and the construction of binodal curves for polyethylene glycols (PEG) + zinc sulfate/ammonium sulfate + water at three different temperatures (298.15, 303.15, and 308.15 K) and pH values (3.00, 4.70, and 5.21). PEGs with different molecular weights of 2000 g·mol–1 (PEG 2000), 3000 g·mol–1 (PEG 3000), and 8000 g·mol–1 (PEG 8000) were chosen for this study. The phase composition was obtained by measuring the refractive index (n D) and dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
(91 reference statements)
2
21
0
Order By: Relevance
“…Pirdashti et al measured the effect of the polymer molecular mass, pH, and temperature on the phase equilibrium of ATPSs of the ternary systems of PEG 2000 , PEG 3000 , and PEG 8000 + zinc sulfate or ammonium sulfate + water at T = 298.15, 303.15, and 308.15 K. The results proved that the two-phase region has been extended by increasing the temperature. In other studies, Pirdashti’s group reported the pH effect on the binodal curves and tie-line compositions of PEG 1500 and PEG 6000 + MgSO 4 + water ATPSs at room temperature. , …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pirdashti et al measured the effect of the polymer molecular mass, pH, and temperature on the phase equilibrium of ATPSs of the ternary systems of PEG 2000 , PEG 3000 , and PEG 8000 + zinc sulfate or ammonium sulfate + water at T = 298.15, 303.15, and 308.15 K. The results proved that the two-phase region has been extended by increasing the temperature. In other studies, Pirdashti’s group reported the pH effect on the binodal curves and tie-line compositions of PEG 1500 and PEG 6000 + MgSO 4 + water ATPSs at room temperature. , …”
Section: Introductionmentioning
confidence: 97%
“…In other studies, Pirdashti's group reported the pH effect on the binodal curves and tie-line compositions of PEG 1500 and PEG 6000 + MgSO 4 + water ATPSs at room temperature. 35,36 In this study, the effect of temperature on the binodal curves and tie-lines of the ternary system containing PEG 2000 + trilithium citrate + water has been measured experimentally and modeled using some appropriate thermodynamic models. Three-parameter nonlinear equations 31 were used to fit binodal curves at the studied temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This approach cannot be applied for polymers of very high crystallinity because they are insoluble in solvents whose solubility parameters perfectly match their own. Statistical assessments of the new model as compared to the methods of Koc−Koç2 5 and Goudarzi et al 24 confirmed that eq 5 has significant reliability.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the new model covers any kind of polymer with high reliability because reliable forecasts always that the coverages are greater than 90%. 46 those predicted by complex QSPR models of Koc−Koç2 5 and Goudarzi et al 24 The predicted absolute percent error (APE) values of eq 5 for 97 polymers were compared with those of the two QSPR methods of Koc−Koç2 5 and Goudarzi et al 24 (Tables S1 and S2). Figure 4 compares the results of eq 5 and the Koc− Koç2 5 and Goudarzi et al 24 methods with the measured data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation